Importance of biological control of pests in corn (Zea mays L.) - Hernández-Trejo, Antonia; Estrada Drouaillet, Benigno; Rodríguez-Herrera, Raúl; García Giron, José Manual; Patiño-Arellano, Sara Alejandra Alejandra; Osorio-Hernández, Eduardo (Revista Mexicana de Ciencias Agrícolas, 2019)
Plague insects are one of the main constraints in the production of corn crops. Therefore, they cause damage to the development of the plant and therefore reduce performance. The armyworm Spodoptera fugiperda J. E. Smith and Heliothis zea (Boddie), (Lepidoptera: Noctuidae) are the most present in the cultivation of corn. For the control of these and other pests, the most used control are chemical insecticides; the main disadvantages of its use have been the contamination of the environment and the resistance of insect pests, this has caused damage to the environment and resistance. An alternative is the use of entomopathogenic microorganisms, predators or parasitoids. Within these are entomopathogenic fungi such as Metarhizum anisopliae (Metchnikoff) Sorokin, and predators of the family Coccinellidae as Cycloneda sangunea (Linnaeus), being these most used in biological control. Also, some parasitoids such as Telenomus remus (Nixon) (Hymenoptera: Platygastridae). Therefore, the advantages of biological control is to reduce levels of pest infestation to a proportion that do not cause economic damage, reduce the spectrum of action and also do not generate pollution to the environment. The biological control depends to a large extent on the climatic conditions, phenological stage of the crop and the interaction between the pests and the host.